Seizure-Induced Arc mRNA Expression Thresholds in Rat Hippocampus and Perirhinal Cortex - Chawla, Monica K.; Gray, Daniel T.; Nguyen, Christie; Dhaliwal, Harshaan; Zempare, Marc; Okuno, Hiroyuki; Huentelman, Matthew J.; Barnes, Carol A. (Frontiers in Systems Neuroscience, 2018)
Immediate-early genes (IEGs) are rapidly and transiently induced following excitatory neuronal activity including maximal electroconvulsive shock treatment. The rapid RNA response can be blocked by the sodium channel antagonist tetrodotoxin, without blocking seizures, indicating a role for electrical stimulation in electroconvulsive shock-induced mRNA responses. In behaving animals, Arc mRNA is selectively transcribed following patterned neuronal activity and rapidly trafficked to dendrites where it preferentially accumulates at active synapses for local translation. Here we examined whether there is a relationship between the current intensities that elicit seizures and the threshold for Arc mRNA transcription in the rat hippocampus and perirhinal cortex (PRC). Animals received electroconvulsive shock treatment (ECT) of varying current intensities (0, 20, 40 65, 77 and 85 mA) and were sacrificed 5 min later. While significantly more CA1, CA3 and perirhinal pyramidal cells expressed Arc at the lowest stimulus intensity compared to granule cells, there was an abrupt threshold transition that occurred in all four regions at 77 mA. This precise threshold for Arc expression in all temporal lobe neurons examined suggests a tight regulation of the calcium-dependent mechanisms that regulate activity-dependent IEG transcription.